Can High Order Thinking Thematic and Critical Thinking Skills Affect Student Learning Outcomes?: A Evidence in Elementary Schools in Grobogan Regency, Central Java - Fanty Wahyu Nurvitasari; Sukartono Sukartono (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2022)
This study aims to analyze the effect of applying thematic HOTS questions and critical thinking skills to the learning outcomes of fourth grade elementary school students in Grobogan Regency. The approach that used by the researcher is a quantitative approach, with an ex post facto model design. This study used a sample of 47 students, instruments in research not only used questionnaires and documentation, but also used validity and reliability tests. Normality and linearity tests are used as perquisite test. T-test is used as simple linear regression hypothesis test, meanwhile F test is used as multiple regression test. The results of this study indicated that; (1) The application of thematic HOTS questions proved to have a significant effect of 14.5% on learning outcomes. (2) Critical thinking skills had a significant effect of 22.9% on learning outcomes. (3) The application of thematic HOTS questions and critical thinking together had a significant effect of 0.33% on learning outcomes. This research implies is that the refraction of higher-order thinking and critical thinking must start from elementary school so that students can keep up with the changes in the 21st century, besides that teachers are also to prepare more creative and innovative teaching materials so that learning occurs that sharpens students to think at a higher level.